Identification of Some Etiological Organisms Causing LRTI in Children Admitted to Central Child Teaching Hospital - Rasha Sulaiman Abdulraheem; Layla Qasim Hiris (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Childhood pneumonia is an important cause of morbidity in the developed world and morbidityand mortality in the developing world. One of the challenges in planning the treatment of respiratory tractinfection in children is identifying the causative agent. The Community Acquired Pneumonia (CAP) presentsboth a diagnostic and therapeutic challenge to clinicians.Aims of the Study: To obtain the epidemiological profile, identify some etiological factors , assess theclinical presentations, x-ray findings and laboratory investigations of children with lower respiratory tractinfection at Child’s Central Teaching Hospital in Baghdad.Patients and Method: A total of 86 children were included in the study. we investigate the etiology of acutelower respiratory tract infection in children under two years admitted to central child teaching hospital fora period of three months in winter. Antibodies of RSV and Chlamydia Pneumonitis were detected usingELISA.Results: Whereas 38 of the children (44%) were diagnosed with pneumonia caused by Chlamydiapneumonitis. RSV was detected in 14 (16%) and 30 (35%) had combined infection .Age of most of thepatients was between one and six months with male predominance. CRP was negative(79%) in the majorityof our patients ,only 3 patients had lower positive titers. WBC differential count show predominance oflymophocytosis (58%) ,which is compatible with viral and atypical lower respiratory tract infection .Conclusion: The identification of the cause of ARI remains challenging, due either to inadequate samplesthat may lead to false negative results, or to difficult interpretation of positive findings between infectionand colonization. In our study the highest rate of acute lower respiratory tract infection was between age ofone and six months with predominance of male sex. Chlamydia microorganism was found in 44% of suchpatients with lower respiratory tract infection. Further studies are needed to identify other possible agents ofARI (e.g., influenza, adenoviruses, other bacterial infections) in this population and to better understand thecausal role of atypical bacteria detected in respiratory samples.